Keteguhan Rekat Geser dan Keteguhan Lengkung Statis Kayu Laminasi dari Kayu Pinus (Pinus merkusii Jungh et de Vr.) dan Kayu Sengon (Paraserianthes falcataria (L) Nielsen) Berperekat Melamins Urea Formaldehida (MUF): The Shear Bond and Bending Strength of Laminated Wood From Pine Wood (Pinus merkusii Jungh et de Vr.,) and Sengon Wood (Paraserianthes falcataria (L) Nielsen) Glued With Melamine Urea Formaldehyde (MUF) - DAYADI, IRVIN (PERENNIAL, 2024)
Laminated wood's strength properties are influenced by the arrangement of each layers. This research aims to determine the effect of variations in layers of laminated wood to the shear bond strength, modulus of elasticity (MoE) and modulus of rupture (MoR) of laminated wood from Pine (P) and Sengon (S) wood using melamine urea formaldehyde adhesive (MUF). Laminated wood is tested using German standards DIN (Deutsches Intitut fur Normung), JAS 234-2007 and SNI 7973-2013. The data testing from 6 layer variation treatments were analyzed of variance in a completely randomized design (CRD) with 10 replications. The highest average value of shear bond strength for laminated wood in treatment G2 (Sengon-Sengon) was 6.17 N/mm2 which met the JAS 234-2007 standard (>5.4 N/mm2) while treatment G3 (Pine-Sengon) was 4.04 N/mm2 and G1 (Pine-Pine) of 2.78 N/mm2 cannot meet the standard. The highest average MoE was at A5 (P-S-S-P-P) at 8584.27 N/mm2 and the lowest at A3 (P-S-P) at 6210.99 N/mm2 included quality codes E8 and E6 in the SNI 7973-2013 Standard. The highest average MoR was at A4 (P-S-S-S-P) at 73.23 N/mm2 and the lowest at A5 (P-S-S-P-P) at 61.98 N/mm2, all treatments included quality code E25 (>25 N/mm2) and could meet JAS 234-2007 Standards (>36.0 N/mm2). The laminated wood in this study based on MoR is included to the strength class III – II and located between the strength class of Pine wood (strength class II) and Sengon wood (strength class III).